2009
DOI: 10.1523/jneurosci.3758-08.2009
|View full text |Cite
|
Sign up to set email alerts
|

The Basolateral Amygdala Is Critical to the Expression of Pavlovian and Instrumental Outcome-Specific Reinforcer Devaluation Effects

Abstract: Considerable evidence implicates the basolateral amygdala (BLA) in the formation of outcome representations that link cues to the incentive properties of reinforcers. Animals with BLA damage show impaired performance in reinforcer devaluation tasks, in which the value of the food reinforcer is reduced by satiation or food-toxin pairings after the completion of cue or response training. Although intact animals spontaneously reduce their conditioned responding after such reinforcer devaluation procedures, animal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
136
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(159 citation statements)
references
References 27 publications
20
136
3
Order By: Relevance
“…In contrast to our results, many studies in appetitive conditioning paradigms indicate that the BLA is importantly involved in revaluing food USs (Hatfield et al 1996;Killcross et al 1997;Blundell et al 2001;Balleine et al 2003;Everitt et al 2003;Pickens et al 2003;Holland 2004;Holland and Gallagher 2004;Johnson et al 2009). One reason the BLA may be important for US revaluation in these paradigms concerns the method used to revalue the US.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to our results, many studies in appetitive conditioning paradigms indicate that the BLA is importantly involved in revaluing food USs (Hatfield et al 1996;Killcross et al 1997;Blundell et al 2001;Balleine et al 2003;Everitt et al 2003;Pickens et al 2003;Holland 2004;Holland and Gallagher 2004;Johnson et al 2009). One reason the BLA may be important for US revaluation in these paradigms concerns the method used to revalue the US.…”
Section: Discussioncontrasting
confidence: 99%
“…Furthermore, recent appetitive studies have found that the BLA is involved in reinforcer devaluation only when multiple reinforcers are used (Wellman et al 2005;Ostlund and Balleine 2008;Johnson et al 2009); BLA manipulations do not influence devaluation when single-outcome associations are learned (Pickens et al 2003). Hence, differences in both the valence and number of USs may influence the degree to which the amygdala is engaged in US revaluation processes.…”
Section: Discussionmentioning
confidence: 99%
“…Motivational behaviors driven by expected pleasantness thus depend upon the episodic memories of prior experiences with the rewards. Research conducted on animals demonstrated that this mechanism relies on a network that includes the basolateral nucleus of the amygdala, which plays a critical role in encoding and updating experienced pleasantness (Johnson et al, 2009;Wassum et al, 2011a,b;Wellman et al, 2005), as well as prelimbic regions of the prefrontal cortex (Balleine and Dickinson, 1998;Killcross and Coutureau, 2003) and dorsomedial regions of the striatum (Yin et al, 2005), which retrieve and compute expected pleasantness to modulate the behavioral output.…”
Section: Differentiating Expected Pleasantness From Affective Relevanmentioning
confidence: 99%
“…Inputs from the BLA are of interest because of data suggesting that the BLA is responsible for assigning motivational significance to stimuli and responses, particularly when animals must discriminate multiple rewards with reference to their sensoryspecific properties Corbit and Balleine, 2005;Balleine and Killcross, 2006;Johnson et al, 2009). Whereas rats with BLA lesions are not impaired in the acquisition of instrumental tasks, they do show deficits in performance following outcome devaluation Corbit and Balleine, 2005).…”
Section: Introductionmentioning
confidence: 99%